Investigating the Relationship between Serum Level of s-Met (Soluble Hepatic Growth Factor Receptor) and Preeclampsia in the First and Second Trimesters of Pregnancy. (31st July 2013) - Naghshvar, Farshad; Torabizadeh, Zhila; Moslemi Zadeh, Narges; Mirbaha, Hooman; Gheshlaghi, Parand
Abstract : Introduction . Preeclampsia (PE) is an important cause of mortality and morbidity for mothers, fetuses, and the newborns. Placenta plays a pivotal role in pathogenesis of PE. Hepatic growth factor (HGF) is a cytokine expressed by the mesenchymal stalk of placental villi during pregnancy and assumes a paracrine role in trophoblasts which express its receptor (c-MET). In the present study, we investigate the diagnostic value of s-Met (the soluble form of the receptor) in the first and second trimesters of pregnancy for early diagnosis of preeclampsia. Method and Materials . This is a case-control study conducted on 95 pregnant women. The serum level of s-Met was measured in the first and second trimesters, and the participants were followed until delivery. 44 individuals with preeclampsia (the case group) and 51 individuals without preeclampsia (the control group) were evaluated. Results . Serum level of s-Met in preeclamptic participants was lower than that of the control group in both the first and the second trimesters (P < 0.0001 ). In addition, serum levels of s-Met were significantly lower during the first and second trimesters in patients with early, severe preeclampsia compared to those with late, mild preeclampsia (P < 0.0001 ). The sensitivity and specificity of s-Met in the first and second trimesters were, respectively, (83%, 94%) and (77%, 94%) for early preeclampsia and (88%, 92%) and (86%, 98%) for severe preeclampsia. Conclusion . Considering our findings, serum level of s-Met may be used as a predictive factor for early detection of preeclampsia. Further research is required to corroborate the functional and therapeutic value of s-Met in preeclampsia.